2018
DOI: 10.1148/radiol.2017170173
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous US-guided Cholecystocholangiography with Microbubbles for Assessment of Infants with US Findings Equivocal for Biliary Atresia and Gallbladder Longer than 1.5 cm: A Pilot Study

Abstract: Purpose To evaluate the feasibility of ultrasonographically (US) guided percutaneous cholecystocholangiography (PCC) for early exclusion of biliary atresia (BA) in infants suspected of having BA with equivocal US findings or indeterminate type of BA and a gallbladder longer than 1.5 cm at US. Materials and Methods This study was approved by the ethics committee; written informed parental consent was obtained. From February 2016 to December 2016, nine infants (four boys, five girls; mean age, 60.2 days; median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…Kaplan-Meier survival curves indicated that the overall survival time with a native liver after KPE between two groups was also not significantly different. SWE value, which is widely used to measure liver stiffness and has the possibility for predicting native liver survival after KPE surgery in patients with isolated BA [11,16,17], was also similar between two groups. And our analyses revealed that most USG characteristics were similar between two groups.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Kaplan-Meier survival curves indicated that the overall survival time with a native liver after KPE between two groups was also not significantly different. SWE value, which is widely used to measure liver stiffness and has the possibility for predicting native liver survival after KPE surgery in patients with isolated BA [11,16,17], was also similar between two groups. And our analyses revealed that most USG characteristics were similar between two groups.…”
Section: Discussionmentioning
confidence: 83%
“…For patients with small gallbladder (shorter than 1.5 cm, n = 6) and absence of gallbladder on USG (n = 5), whether the cyst communicated with the gallbladder wasn't confirmed by intraoperative cholangiography, because it is generally impossible to perform intraoperative cholangiography in these patients. In addition, two patients with cyst communicated with the gallbladder were confirmed by the percutaneous ultrasound-guided cholecystocholangiography with microbubbles, a mature technology in our center [11]. Figure 1 shows a 9-day-old female with a 28 mm × 16 mm porta cyst that was communicated with the gallbladder from a small tube (approximately 2 mm diameter) ( Fig.…”
Section: Ultrasonography Technique and Imaging Analysismentioning
confidence: 83%
“…As one of the most widely used ultrasound features for the diagnosis of BA, gallbladder abnormalities have been greatly emphasized by many investigators, due to their high sensitivity in distinguishing BA from other neonatal jaundice conditions . Most features would require infants to be fasted for at least 4 hours before being examined via ultrasonography to more clearly detect and measure the gallbladder . However, our previous studies have shown that an incompletely filled gallbladder, detected via ultrasonography, can also help in excluding BA.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnoses of the 100 infants with BA were confirmed by using surgical exploration (n = 90), liver biopsy (n = 7), or intraoperative cholangiography under laparoscopy (n = 3). The 88 infants without BA were diagnosed by using intraoperative cholangiography (n = 29), liver biopsy (n = 3), percutaneous ultrasound‐guided cholecystocholangiography (n = 4), or clinical follow‐up (n = 52). The jaundice conditions in infants without BA were completely resolved during a follow‐up period of 2 weeks to 12 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation